The sural-sparing pattern in clinical variants and electrophysiological subtypes of Guillain-Barré syndrome - Castro, Vinicius Furtado da Silva; Oliveira, Roberto Teodoro Gurgel de; Santos, João Daniel Lima dos; Mendes, Ramon de Souza; Pessoa Neto, Agábio Diógenes; Fidelix, Emanuela Coriolano; Dourado Júnior, Mário Emílio Teixeira (Arquivos de Neuro-Psiquiatria, 2024)
Background Guillain-Barré syndrome (GBS) is the most common cause of acute flaccid paralysis worldwide and can be classified into electrophysiological subtypes and clinical variants.Objective This study aimed to compare the frequency of the sural-sparing pattern (SSP) in subtypes and variants of GBS.Methods This retrospective cohort study analyzed clinical and electrophysiological data of 171 patients with GBS hospitalized in public and private hospitals of Natal, Rio Grande do Norte, Brazil, between 1994 and 2018; all cases were followed up by the same neurologist in a reference neurology center. Patients were classified according to electrophysiological subtypes and clinical variants, and the SSP frequency was compared in both categories. The exact Fisher test and Bonferroni correction were used for statistical analysis.Results The SSP was present in 53% (57 of 107) of the patients with acute inflammatory demyelinating polyradiculoneuropathy (AIDP), 8% (4 of 48) of the patients with axonal subtypes, and 31% (5 of 16) of the equivocal cases. The SSP frequency in the AIDP was significantly higher than in the axonal subtypes (p < 0.0001); the value was kept high after serial electrophysiological examinations. Only the paraparetic subtype did not present SSP.Conclusion The SSP may be present in AIDP and axonal subtypes, including acute motor axonal neuropathy, but it is significantly more present in AIDP. Moreover, the clinical variants reflect a specific pathological process and are correlated to its typical electrophysiological subtype, affecting the SSP frequency.
Keywords: Guillain-Barré Syndrome; Nerve Conduction Studies; Sural Nerve; Neurophysiology; Peripheral Nervous System Diseases